2011
DOI: 10.1111/j.1468-1331.2011.03542.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of spontaneous non‐aneurysmal subarachnoid hemorrhage in 108 patients

Abstract: Non-aneurysmal SAH with a perimesencephalic pattern of bleeding has a benign course and excellent short-term and long-term prognosis. Patients with non-aneurysmal SAH with an aneurysmal pattern of bleeding have more complications, and the initial clinical situation has a significant impact on their prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 17 publications
4
39
0
Order By: Relevance
“…In the current series, patients with NPM-SAH or PM-SAH had a different outcome. Patients with PM-SAH had an excellent outcome, as in other series,7 8 15 16 21 24–26 which also confirmed that the patients were classified correctly. However, excluding Fi3 (favorable outcome in only 71% of the patients; table 1), patients with NASAH without Fi3 also had an excellent chance of a favorable outcome, similar to patients with PM-SAH (both about 90%; table 2).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the current series, patients with NPM-SAH or PM-SAH had a different outcome. Patients with PM-SAH had an excellent outcome, as in other series,7 8 15 16 21 24–26 which also confirmed that the patients were classified correctly. However, excluding Fi3 (favorable outcome in only 71% of the patients; table 1), patients with NASAH without Fi3 also had an excellent chance of a favorable outcome, similar to patients with PM-SAH (both about 90%; table 2).…”
Section: Discussionsupporting
confidence: 79%
“…Also, in about 15–25% of patients with subarachnoid hemorrhage (SAH), cerebral angiography, CT scan, and spinal MRI are negative for aneurysms or other vascular malformations 2–5. Data from series with small patient numbers showed a similar outcome between perimesencephalic (PM) and non-PM (NPM) SAH but larger series, maybe due to the improved statistical power, identified different outcomes between PM-SAH and NPM-SAH 6 7. In a recent review of PM-SAH, most series had a patient cohort of about 50 patients and only one paper had a cohort of more than 150 patients 8.…”
Section: Introductionmentioning
confidence: 99%
“…However, data on patients with spontaneous NASAH are commonly based on case series and are therefore rare . But even more, data assessing the long‐term outcome are scarce and lacking for physiological and psychological outcome in a series with more than 50 patients. Our neurovascular database was therefore analyzed concerning patients suffering from NASAH.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysm, arteriovenous malformation and cavernous malformation are the most common causes of non-traumatic intracranial hemorrhages [3][4][5]. Conventional catheter angiography is the gold standard for diagnosis of vascular abnormality; however; other imaging modalities such as CTA and MRA can help to find out about vascular abnormalities [6][7][8]. Intracranial aneurysms are the most common causes of non-traumatic intracranial hemorrhage, occurring in 60%-85% of cases [9,10].…”
Section: Introductionmentioning
confidence: 99%